Is resilience to climate change socially inclusive? Investigating theories of change processes in Myanmar. (November 2018) - Forsyth, Tim
Highlights: Theories of change for resilience often exclude local experiences of risk. Risks are experienced unequally by people of different socio-economic status. Anticipatory capacity for resilience can overlook socio-economic inequalities. Theories of change need to make socio-economic transformation more explicit. The role of resilience as an uncontested boundary object needs more attention. Abstract: Approaches to resilience to climate change can be socially exclusionary if they do not acknowledge diverse experiences of risks or socio-economic barriers to resilience. This paper contributes to analyses of resilience by studying how theories of change (ToC) processes used by development organizations might lead to social exclusions, and seeking ways to make these more inclusive. Adopting insights from participatory monitoring and evaluation, the paper first presents fieldwork from four villages in Myanmar to compare local experiences of risk and resilience with the ToCs underlying pathways to resilience based on building anticipatory, absorptive, and adaptive capacities. The paper then uses interviews with the development organizations using these pathways to identify how ToC processes might exclude local experiences and causes of risk, and to seek ways to make processes more inclusive. The research finds that development organizations can contribute to shared ToCs for resilience, but adopt tacitly different models of risk that reduce attention to more transformative socio-economic pathways to resilience. Consequently, there is a need to consider how resilience and ToCs can become insufficiently scrutinized boundary objects when they are shared by actors with different models of risk and intervention.